Organizational management from the perspective of public health: exploring the strategies to improve staff's work enthusiasm and efficiency - Yang, Zhou (Frontiers in Psychology, 2025)
BackgroundIn the evolving landscape of organizational management, employee psychological wellbeing plays a crucial role in driving workforce efficiency and performance. In China, especially within institutions such as universities and public service organizations, this aspect is often underemphasized. This study investigates the relationship between psychological states and employee productivity in the context of Chinese organizational settings.MethodsWe conducted a comprehensive analysis based on psychological assessments, employee interviews, and case studies within selected Chinese institutions. Key psychological indicators such as flow state, anxiety, and stress levels were evaluated, and their influence on employee work force and efficiency was examined.ResultsThe analysis reveals a strong correlation between employees' psychological states and their work outcomes. A positive flow state significantly enhances work motivation and creativity, while anxiety and excessive stress hinder efficiency. Targeted strategies including goal-setting, resource provision, environmental support, and psychological tracking mechanisms proved effective in improving overall staff performance.ConclusionsIntegrating psychological state analysis into organizational management practices is essential for fostering a productive workforce. This study provides actionable insights for managers and policy-makers in China, emphasizing the value of mental health support, structured workflow optimization, and cultural environment enhancement to sustainably boost employee motivation and organizational performance.